Low shrinkage fire resistant material for crosslinked polyethylene power cables
Patent Information
- Application Number
- CN202611441610.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-17
- Publication Date
- 2026-10-20
AI Technical Summary
[0004]然而,小分子偶联剂在高温下易水解脱附,界面增容效果随时间衰减,物理共混的阻燃剂迁移析出严重,造成阻燃效率下降及表面喷霜,各向同性填料缺乏定向钉扎结构,低收缩效果有限,更关键的是,传统技术难以同时实现无机-有机共价交联、阻燃单元化学锚定及各向异性填料的取向锁定,导致低收缩与阻燃性能难以协同提升
[0025]1、本发明是在改性硅灰石表面聚硅氧烷壳层保留的游离氨基与马来酸酐接枝聚烯烃经酰化反应形成酰胺键交联网络,硅灰石晶须在挤出剪切场中沿轴向取向产生各向异性物理钉扎,聚硅氧烷壳层作为梯度模量界面缓冲热应力,协同抑制分子链滑移及解取向松弛,显著降低径向热收缩率,且高温热循环下界面无脱粘,低收缩性能具有持久稳定性。
Abstract
Description
Technical Field
[0001] This invention relates to the field of cable processing technology, and specifically to a low-shrinkage refractory material for cross-linked polyethylene power cables. Background Technology
[0002] The dimensional stability and flame retardant properties of cross-linked polyethylene power cable sheath materials directly determine the safety of the line. With the increase in power grid load and the increasing complexity of the laying environment, the industry has increasingly stringent requirements for the synergistic performance of low shrinkage and fire resistance of the sheath. If the thermal shrinkage rate of traditional materials is too high after extrusion, it can easily lead to gaps between the sheath and the conductor, partial discharge and moisture intrusion. At the same time, it is necessary to have sufficient fire resistance to maintain the integrity of the line in the event of a short circuit or fire.
[0003] Currently, most flame retardants are based on POE, EVA, or polyethylene, compounded with magnesium hydroxide, ammonium polyphosphate, zinc borate, etc., and supplemented with fillers such as wollastonite and glass fiber to reduce shrinkage. In order to improve interfacial compatibility, silane coupling agents are often used to pretreat the fillers, or maleic anhydride is grafted onto polyolefins for physical compatibility enhancement. Phosphorus- and nitrogen-containing flame retardants are mostly added directly to the matrix by physical blending.
[0004] However, small molecule coupling agents are prone to hydrolysis and desorption at high temperatures, and the interfacial compatibilization effect decays over time. Physically blended flame retardants migrate and precipitate severely, resulting in decreased flame retardant efficiency and surface blooming. Isotropic fillers lack directional pinning structures, resulting in limited low shrinkage effects. More importantly, traditional technologies cannot simultaneously achieve inorganic-organic covalent crosslinking, chemical anchoring of flame retardant units, and orientation locking of anisotropic fillers, making it difficult to synergistically improve low shrinkage and flame retardant performance.
[0005] To address this technical deficiency, a solution is proposed. Summary of the Invention
[0006] This invention addresses the technical problem that the low shrinkage and flame-retardant properties of cross-linked polyethylene power cable sheathing materials in the prior art need further improvement.
[0007] The objective of this invention can be achieved through the following technical solution: a low-shrinkage refractory material for cross-linked polyethylene power cables, comprising the following components by weight: 80-100 parts of POE, 20-30 parts of modified wollastonite, 4-6 parts of phosphaphenanthrene epoxy derivative, 18-25 parts of maleic anhydride-grafted POE, 35-50 parts of flame retardant synergist, and 0.5-1.0 parts of processing aid;
[0008] The modified wollastonite is prepared by: placing amino-terminated polydimethylsiloxane and xylene in a reaction vessel and stirring, adding epoxy-modified wollastonite whiskers, heating the reaction vessel to 75-85℃, maintaining the temperature and stirring for 4-5 hours, and then processing to obtain the modified wollastonite.
[0009] The ratio of amino-terminated polydimethylsiloxane, xylene, and epoxy-modified wollastonite whiskers is 1-2g:10-20mL:2-4g. The post-processing steps include: after the reaction is completed, the reaction system is cooled to room temperature, filtered, the filter cake is washed with ethanol 1-3 times, transferred to a vacuum drying oven at 60-70℃, and dried to constant weight to obtain modified wollastonite.
[0010] Furthermore, the preparation method of the phosphenanthrene epoxy derivative is as follows: 9,10-dihydro-9-oxa-10-phosphenanthrene-10-oxide, allyl glycidyl ether and toluene are placed in a reaction vessel under nitrogen atmosphere and stirred. The reaction vessel is heated to 90-100℃ and kept at this temperature for 5-7 hours. The phosphenanthrene epoxy derivative is then obtained after post-treatment.
[0011] Furthermore, the ratio of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, allyl glycidyl ether, and toluene is 1-2 g: 0.45-0.50 g: 8-12 mL. The post-processing steps include: after the reaction is completed, the pressure is reduced to -0.08 MPa to -0.09 MPa, and toluene is recovered by distillation for 2-3 hours. Then, the vacuum degree is increased to -0.095 MPa to -0.099 MPa, the temperature of the reaction vessel is increased to 100-110°C, and the pressure distillation is continued for 1-2 hours. After no more distillate is distilled off, heating is stopped, and the remaining material is cooled to room temperature under nitrogen protection to obtain the phosphaphenanthrene epoxy derivative.
[0012] Furthermore, the epoxy-modified wollastonite whiskers are prepared by the following steps:
[0013] A1. Place wollastonite whiskers and hydrochloric acid aqueous solution in a reaction vessel and stir. Heat the reaction vessel to 30-50℃ and stir for 0.5-1h. Post-treatment yields epoxy-modified wollastonite whisker precursor.
[0014] A2. Place γ-glycidyl etheroxypropyltrimethoxysilane, tetraethyl orthosilicate, ethanol, deionized water and glacial acetic acid aqueous solution in a reaction vessel and stir at room temperature for 0.5-1 h to obtain epoxy-containing polysiloxane sol.
[0015] A3. Place the epoxy-modified wollastonite whisker precursor and the epoxy-containing polysiloxane sol in a reaction vessel and stir. Heat the reaction vessel to 55-65℃ and keep it at that temperature for 2-4 hours. After post-treatment, epoxy-modified wollastonite whiskers are obtained.
[0016] Further, in step A1, the ratio of wollastonite whiskers to hydrochloric acid aqueous solution is 1-2g:8-15mL, and the concentration of hydrochloric acid aqueous solution is 0.3-0.5mol / L. The post-processing steps include: after the reaction is completed, the reaction system is cooled to room temperature, filtered, the filter cake is washed with deionized water until neutral, transferred to a vacuum drying oven at 100-120℃, and dried to constant weight to obtain epoxy-modified wollastonite whisker precursor.
[0017] Furthermore, in step A2, the ratio of the amounts of γ-glycidoxypropyltrimethoxysilane, tetraethyl orthosilicate, ethanol, deionized water, and glacial acetic acid aqueous solution is 1.5-2.5g:0.2-0.5g:30-50mL:2-4mL:0.03-0.05g, and the concentration of the glacial acetic acid aqueous solution is 3-5wt%.
[0018] Further, in step A3, the ratio of the epoxy-modified wollastonite whisker precursor to the epoxy-containing polysiloxane sol is 8-10g:200-300mL. The post-processing steps include: after the reaction is completed, the reaction system is cooled to room temperature, the filter cake is washed with ethanol 2-4 times, transferred to a vacuum drying oven at 80-100℃, and dried to constant weight to obtain epoxy-modified wollastonite whiskers.
[0019] The present invention also proposes a method for preparing a low-shrinkage refractory material for cross-linked polyethylene power cables, comprising the following steps:
[0020] S1. Add POE, modified wollastonite, flame retardant synergist and processing aid to a high-speed mixer and mix at a low speed of 300-500 rpm for 3-5 minutes at room temperature. Then add maleic anhydride-grafted POE and phosphaphenanthrene epoxy derivative, increase the speed to 800-1000 rpm and mix at a high speed for 3-5 minutes to obtain the initial mixture.
[0021] S2. Add the initial mixture to the feed hopper of the twin-screw extruder. The material stays in the high-temperature and high-shear zone for 1.5-2.5 minutes. The melt is extruded into strips through the die head, cooled and dried in a 25-30℃ water bath, and cut into 2-4mm cylindrical particles by a pelletizer. The particles are then dried in hot air at 60-70℃ for 3-5 hours to obtain low-shrinkage refractory material.
[0022] Further, in step S1, the flame retardant synergist is composed of magnesium hydroxide, ammonium polyphosphate, and zinc borate in a mass ratio of 25-35:8-12:3-5; the processing aid is composed of antioxidant, lubricant, and catalyst in a mass ratio of 2:2:1; the antioxidant is one or more of pentaerythritol tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], tris(2,4-di-tert-butylphenyl) phosphite, and octadecyl β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate; the lubricant is one or more of ethylene bis-stearamide, polyethylene wax, and zinc stearate; and the catalyst is one or more of 2-methylimidazole, tetrabutylammonium bromide, and N,N-dimethylbenzylamine.
[0023] Furthermore, in step S2, the temperature of the twin-screw extruder is: 160-170℃ in zone 1, 175-185℃ in zone 2, 190-200℃ in zone 3, 195-205℃ in zone 4, 190-195℃ at the die head, and the screw speed is 280-350 rpm.
[0024] The present invention has the following beneficial effects:
[0025] 1. The present invention involves the formation of an amide bond crosslinking network by acylation of free amino groups retained in the polysiloxane shell layer on the surface of modified wollastonite with maleic anhydride-grafted polyolefins. During the extrusion shear field, the wollastonite whiskers are anisotropically pinned along the axial orientation. The polysiloxane shell layer acts as a gradient modulus interface to buffer thermal stress, synergistically suppressing molecular chain slippage and disorientation relaxation, significantly reducing the radial thermal shrinkage rate. Moreover, there is no interface debonding under high temperature thermal cycling, and the low shrinkage performance has long-lasting stability.
[0026] 2. The phosphenanthrene epoxy derivative of this invention is bonded to the matrix network through the esterification reaction of terminal epoxy groups with anhydride-functionalized polyolefins. It forms a PN-Si-B multi-component synergistic flame-retardant system with ammonium polyphosphate, magnesium hydroxide, and zinc borate. During combustion, the bonded phosphenanthrene ring promotes dehydration and char formation in the matrix, while ammonium polyphosphate releases phosphorus-containing free radicals to interrupt the gas-phase chain reaction. Polysiloxane and zinc borate on the wollastonite surface provide a silicate ceramic framework and a borosilicate glass sealing layer, respectively. All components are chemically anchored and uniformly dispersed without migration or precipitation, synergistically constructing a dense and continuous ceramicized thermal insulation barrier.
[0027] 3. The epoxy-modified wollastonite of the present invention is coated with sol-gel to form an epoxy-rich structure. The terminal amino polysiloxane constructs a flexible shell containing free amino groups on its surface through ring-opening addition, thereby forming a Si-O-Si and CN double covalent interface with the matrix. This interface strengthens the inorganic and organic mechanical interlocking, significantly improves tensile strength and elongation at break, and ensures the thermo-oxidative stability and processing behavior controllability of polyolefins under high temperature shear by compounding antioxidants and lubricants, so that the material maintains synchronous stability of mechanical and flame retardant properties during long-term use. Detailed Implementation
[0028] The technical solution of the present invention will be clearly and completely described below with reference to the embodiments. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0029] The wollastonite whiskers used in this invention are commercially available materials with an average diameter of 1-5 μm and an aspect ratio of 15-20:1.
[0030] The amino-terminated polydimethylsiloxane used in this invention is a commercially available material with a number-average molecular weight of 3000-8000 and an ammonia value of 0.6-1.2 mmol / g.
[0031] The maleic anhydride-grafted POE used in this invention is a commercially available material with a maleic anhydride grafting rate of 0.8-1.5wt% and a melt flow rate of 1-10g / 10min.
[0032] The POE used in this invention is a commercially available ethylene-octene copolymer with a density of 0.87-0.90 g / cm³. 3 The melt flow rate is 0.5-5 g / 10 min, and the octene content is 20-45 wt%.
[0033] The magnesium hydroxide used in this invention is a commercially available material with an average particle size of 2-5 μm.
[0034] The ammonium polyphosphate used in this invention is a commercially available material with a degree of polymerization n > 1000, is type II crystallized, and has an average particle size ≤ 10 μm.
[0035] Example 1
[0036] This embodiment provides a method for preparing epoxy-modified wollastonite whiskers, specifically including the following steps:
[0037] Step I: Preparation of epoxy-modified wollastonite whisker precursor
[0038] Weigh 10g of wollastonite whiskers and 80mL of 0.3mol / L hydrochloric acid aqueous solution and place them in a reaction vessel. Stir the reaction vessel to 30℃ and stir for 0.5h. After the reaction is complete, wait for the reaction system to cool to room temperature, filter, wash the filter cake with deionized water until neutral, transfer it to a vacuum drying oven at 100℃ and dry it to constant weight to obtain epoxy-modified wollastonite whisker precursor.
[0039] Step II: Preparation of epoxy-containing polysiloxane sol
[0040] Weigh out 15g of γ-glycidoxypropyltrimethoxysilane, 2g of tetraethyl orthosilicate, 300mL of ethanol, 20mL of deionized water and 0.3g of 3wt% glacial acetic acid aqueous solution and place them in a reaction vessel. Stir at room temperature for 0.5h to obtain epoxy-containing polysiloxane sol.
[0041] Step III: Preparation of epoxy-modified wollastonite whiskers
[0042] Weigh 80g of epoxy-modified wollastonite whisker precursor and 2000mL of epoxy-containing polysiloxane sol and place them in a reaction vessel and stir. Heat the reaction vessel to 55℃ and keep it at that temperature for 2 hours. After the reaction is complete, wait for the reaction system to cool to room temperature, wash the filter cake twice with ethanol, transfer it to a vacuum drying oven at 80℃, and dry it to constant weight to obtain epoxy-modified wollastonite whiskers.
[0043] Dilute hydrochloric acid is used to selectively etch the surface of wollastonite whiskers to dissolve carbonate impurities and expose active silanol groups. γ-glycidoxypropyltrimethoxysilane and tetraethyl orthosilicate are hydrolyzed and condensed under weak acid catalysis to form an epoxy-containing polysiloxane sol. The silanol groups in the sol undergo a dehydration condensation reaction with the silanol groups on the acid-etched and activated whisker surface. An epoxy-containing polysiloxane coating layer is constructed in situ through Si-O-Si covalent bonds to obtain epoxy-modified wollastonite whiskers.
[0044] By increasing the surface roughness and active site density of whiskers, the mechanical interlocking of the organic-inorganic interface is strengthened, and the irreversible deformation caused by interfacial debonding under thermal cycling is suppressed. Epoxy-containing polysiloxane sols are prepared to further regulate the crosslinking density of the coating layer and the surface epoxy functionality, balancing the interfacial reactivity and shell flexibility. Finally, an epoxy-rich core-shell structure is constructed on the whisker surface, providing high-density reaction sites for the chemical grafting of terminal amino polysiloxanes, achieving covalent bridging between the inorganic phase and the polyolefin matrix, and forming an anisotropic physical pinning-chemical crosslinking synergistic anti-shrinkage network.
[0045] Example 2
[0046] This embodiment provides a method for preparing epoxy-modified wollastonite whiskers, specifically including the following steps:
[0047] Step I: Preparation of epoxy-modified wollastonite whisker precursor
[0048] Weigh 15g of wollastonite whiskers and 110mL of 0.4mol / L hydrochloric acid aqueous solution and place them in a reaction vessel. Stir the reaction vessel to 40℃ and stir for 1h. After the reaction is complete, wait for the reaction system to cool to room temperature, filter, wash the filter cake with deionized water until neutral, transfer it to a vacuum drying oven at 110℃ and dry it to constant weight to obtain epoxy-modified wollastonite whisker precursor.
[0049] Step II: Preparation of epoxy-containing polysiloxane sol
[0050] Weigh out 20g of γ-glycidoxypropyltrimethoxysilane, 3.5g of tetraethyl orthosilicate, 400mL of ethanol, 30mL of deionized water and 0.4g of 4wt% glacial acetic acid aqueous solution and place them in a reaction vessel. Stir at room temperature for 1h to obtain epoxy-containing polysiloxane sol.
[0051] Step III: Preparation of epoxy-modified wollastonite whiskers
[0052] Weigh 90g of epoxy-modified wollastonite whisker precursor and 2500mL of epoxy-containing polysiloxane sol and place them in a reaction vessel. Stir the reaction vessel and heat it to 60℃. Keep it at this temperature and stir for 3 hours. After the reaction is complete, wait for the reaction system to cool to room temperature. Wash the filter cake three times with ethanol and transfer it to a vacuum drying oven at 90℃. Dry it to constant weight to obtain epoxy-modified wollastonite whiskers.
[0053] Example 3
[0054] This embodiment provides a method for preparing epoxy-modified wollastonite whiskers, specifically including the following steps:
[0055] Step I: Preparation of epoxy-modified wollastonite whisker precursor
[0056] Weigh 20g of wollastonite whiskers and 150mL of 0.5mol / L hydrochloric acid aqueous solution and place them in a reaction vessel. Stir the reaction vessel to 50℃ and stir for 1h. After the reaction is complete, wait for the reaction system to cool to room temperature, filter, wash the filter cake with deionized water until neutral, transfer it to a vacuum drying oven at 120℃ and dry it to constant weight to obtain epoxy-modified wollastonite whisker precursor.
[0057] Step II: Preparation of epoxy-containing polysiloxane sol
[0058] Weigh out 25g of γ-glycidoxypropyltrimethoxysilane, 5g of tetraethyl orthosilicate, 500mL of ethanol, 40mL of deionized water and 0.5g of 5wt% glacial acetic acid aqueous solution and place them in a reaction vessel. Stir at room temperature for 1h to obtain epoxy-containing polysiloxane sol.
[0059] Step III: Preparation of epoxy-modified wollastonite whiskers
[0060] Weigh 100g of epoxy-modified wollastonite whisker precursor and 3000mL of epoxy-containing polysiloxane sol and place them in a reaction vessel and stir. Heat the reaction vessel to 65℃ and keep it at that temperature for 4 hours. After the reaction is complete, wait for the reaction system to cool to room temperature. Wash the filter cake with ethanol 4 times and transfer it to a vacuum drying oven at 100℃. Dry it to constant weight to obtain epoxy-modified wollastonite whiskers.
[0061] Example 4
[0062] This embodiment provides a method for preparing modified wollastonite, specifically including the following steps:
[0063] Weigh 10g of amino-terminated polydimethylsiloxane and 100mL of xylene and place them in a reaction vessel and stir. Add 20g of epoxy-modified wollastonite whiskers prepared in Example 1. Heat the reaction vessel to 75°C and stir for 4 hours. After the reaction is complete, wait for the reaction system to cool to room temperature, filter, wash the filter cake once with ethanol, transfer it to a vacuum drying oven at 60°C, and dry it to constant weight to obtain modified wollastonite.
[0064] The primary amino groups of amino-terminated polydimethylsiloxane undergo a ring-opening addition reaction with the epoxy groups on the surface of epoxy-modified wollastonite whiskers to generate CN bonds and hydroxyl groups, forming a polysiloxane coating layer. Excess amino groups allow the polysiloxane chains to retain free amino groups, resulting in modified wollastonite.
[0065] By functionalizing the surface of the polysiloxane shell, an inorganic-organic gradient interface is constructed to buffer thermal stress and suppress interface failure. The retained terminal amino groups provide sites for chemical crosslinking with anhydride-functionalized polyolefins during the melt processing stage, forming a covalent anchoring network to constrain molecular chain slip. The siloxane backbone acts as a high-temperature ceramicization precursor, promoting the in-situ formation of a silicon-carbon hybrid protective layer during combustion.
[0066] Example 5
[0067] This embodiment provides a method for preparing modified wollastonite, specifically including the following steps:
[0068] Weigh 15g of amino-terminated polydimethylsiloxane and 150mL of xylene and place them in a reaction vessel and stir. Add 30g of epoxy-modified wollastonite whiskers prepared in Example 2. Heat the reaction vessel to 80℃ and stir for 4.5h. After the reaction is complete, wait for the reaction system to cool to room temperature, filter, wash the filter cake twice with ethanol, transfer it to a vacuum drying oven at 65℃, and dry it to constant weight to obtain modified wollastonite.
[0069] Example 6
[0070] This embodiment provides a method for preparing modified wollastonite, specifically including the following steps:
[0071] Weigh 20g of amino-terminated polydimethylsiloxane and 200mL of xylene and place them in a reaction vessel and stir. Add 40g of epoxy-modified wollastonite whiskers prepared in Example 3. Heat the reaction vessel to 85℃ and keep it at that temperature for 5 hours. After the reaction is complete, wait for the reaction system to cool to room temperature, filter it, wash the filter cake three times with ethanol, transfer it to a vacuum drying oven at 70℃, and dry it to constant weight to obtain modified wollastonite.
[0072] Example 7
[0073] This embodiment provides a method for preparing a phosphenanthrene epoxy derivative, specifically including the following steps:
[0074] Weigh 10 g of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, 4.5 g of allyl glycidyl ether, and 80 mL of toluene into a reaction vessel under nitrogen atmosphere and stir. Heat the reaction vessel to 90 °C and maintain the temperature for 5 h. After the reaction is complete, reduce the pressure to -0.08 MPa and distill to recover toluene for 2 h. Then increase the vacuum to -0.095 MPa and raise the temperature of the reaction vessel to 100 °C. Continue to distill under reduced pressure for 1 h. After no more distillate is distilled off, stop heating and cool the remaining material to room temperature under nitrogen atmosphere to obtain the phosphaphenanthrene epoxy derivative.
[0075] 9,10-Dihydro-9-oxa-10-phosphaphenanthrene-10-oxides add carbon-carbon double bonds to allyl glycidyl ether via pH bonds to form phosphaphenanthrene epoxy derivatives with phosphaphenanthrene rings in the side chain and epoxy groups retained at the end.
[0076] By introducing phosphorus-containing flame-retardant units into reactive epoxy monomers in the form of covalent bonds, they are endowed with the condensed-phase flame-retardant function of promoting matrix dehydration and char formation at high temperatures. The terminal epoxy groups undergo ring-opening esterification reaction with anhydride-functionalized polyolefins during the melt processing stage, realizing the chemical anchoring of phosphorus heterophenanthrene rings in the matrix network, inhibiting migration and precipitation during processing and use, and forming a gas-phase-condensed-phase synergistic flame-retardant system with ammonium polyphosphate.
[0077] Example 8
[0078] This embodiment provides a method for preparing a phosphenanthrene epoxy derivative, specifically including the following steps:
[0079] Weigh 15 g of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, 4.7 g of allyl glycidyl ether, and 100 mL of toluene into a reaction vessel under nitrogen atmosphere and stir. Heat the reaction vessel to 95 °C and maintain the temperature for 6 h. After the reaction is complete, reduce the pressure to -0.085 MPa and distill to recover toluene for 2.5 h. Then increase the vacuum to -0.097 MPa and raise the temperature of the reaction vessel to 105 °C. Continue to distill under reduced pressure for 1.5 h. After no more distillate is distilled off, stop heating and cool the remaining material to room temperature under nitrogen atmosphere to obtain the phosphaphenanthrene epoxy derivative.
[0080] Example 9
[0081] This embodiment provides a method for preparing a phosphenanthrene epoxy derivative, specifically including the following steps:
[0082] Weigh 20g of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, 5g of allyl glycidyl ether, and 120mL of toluene into a reaction vessel under nitrogen atmosphere and stir. Heat the reaction vessel to 100℃ and maintain the temperature for 7h. After the reaction is complete, reduce the pressure to -0.09MPa and distill to recover toluene for 3h. Then increase the vacuum to -0.099MPa and raise the temperature of the reaction vessel to 110℃. Continue to distill under reduced pressure for 2h. After no more distillate is distilled off, stop heating and cool the remaining material to room temperature under nitrogen atmosphere to obtain the phosphaphenanthrene epoxy derivative.
[0083] Example 10
[0084] This embodiment provides a method for preparing a low-shrinkage refractory material for cross-linked polyethylene power cables, specifically including the following steps:
[0085] Step S1: Preparation of initial mixture
[0086] Magnesium hydroxide, ammonium polyphosphate and zinc borate were mixed evenly in a mass ratio of 25:8:3 to obtain a flame retardant synergist for later use.
[0087] Pentaerythritol tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], ethylene bis-stearamide and 2-methylimidazole were mixed evenly in a mass ratio of 2:2:1 to obtain a processing aid for later use.
[0088] Weigh out the following by weight: 80 parts of POE, 20 parts of modified wollastonite prepared in Example 4, 35 parts of flame retardant synergist, and 0.5 parts of processing aid. Add them to a high-speed mixer and mix at a low speed of 300 rpm for 3 minutes at room temperature. Then add 18 parts of maleic anhydride-grafted POE and 4 parts of phosphenanthrene epoxy derivative prepared in Example 7. Increase the speed to 800 rpm and mix at a high speed for 3 minutes to obtain the initial mixture.
[0089] Step S2: Preparation of low-shrinkage refractory materials
[0090] The initial mixture is added to the feed hopper of a twin-screw extruder. The material stays in the high-temperature and high-shear zone for 1.5 minutes. The melt is extruded into strips through the die head, cooled and dried in a 25°C water bath, and cut into 2mm cylindrical particles by a pelletizer. The particles are then dried in hot air at 60°C for 3 hours to obtain a low-shrinkage refractory material.
[0091] The twin-screw extruder temperatures are: Zone 1 160℃, Zone 2 175℃, Zone 3 190℃, Zone 4 195℃, Die head 190℃, and screw speed 280 rpm.
[0092] The initial mixture is melt-plasticized in the high-temperature, high-shear zone of a twin-screw extruder. The free amino groups on the surface of the modified wollastonite undergo an acylation reaction with the anhydride groups of maleic anhydride-grafted POE. The terminal epoxy groups of the phosphenanthrene epoxy derivative undergo a ring-opening esterification reaction with the anhydride groups, constructing an inorganic-organic covalent cross-linked network. 2-methylimidazole catalyzes the anhydride-amine / epoxy reaction, antioxidants inhibit the thermo-oxidative degradation of POE, and lubricants regulate the melt processing behavior, ultimately yielding a low-shrinkage refractory material.
[0093] In the melt extrusion stage, inorganic whiskers are locked in the polyolefin matrix through a chemical anchoring network, giving the material anisotropic shrinkage resistance. Phosphorus-containing flame retardant units are covalently bonded to the matrix network, inhibiting migration and precipitation during processing and service. The multi-component flame retardant system is uniformly dispersed in the matrix, constructing a gas-phase-condensed-phase synergistic flame retardant and high-temperature ceramic barrier. The compounded additive system ensures the thermo-oxidative stability of polyolefin under high-temperature shear and the controllability of melt processing behavior.
[0094] Example 11
[0095] This embodiment provides a method for preparing a low-shrinkage refractory material for cross-linked polyethylene power cables, specifically including the following steps:
[0096] Step S1: Preparation of initial mixture
[0097] Magnesium hydroxide, ammonium polyphosphate and zinc borate were mixed evenly in a mass ratio of 30:10:4 to obtain a flame retardant synergist for later use.
[0098] Pentaerythritol tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], ethylene bis-stearamide and 2-methylimidazole were mixed evenly in a mass ratio of 2:2:1 to obtain a processing aid for later use.
[0099] Weigh out the following by weight: 90 parts of POE, 25 parts of modified wollastonite prepared in Example 5, 42 parts of flame retardant synergist, and 0.7 parts of processing aid. Add them to a high-speed mixer and mix at a low speed of 400 rpm for 4 minutes at room temperature. Then add 22 parts of maleic anhydride-grafted POE and 5 parts of phosphenanthrene epoxy derivative prepared in Example 8. Increase the speed to 900 rpm and mix at a high speed for 4 minutes to obtain the initial mixture.
[0100] Step S2: Preparation of low-shrinkage refractory materials
[0101] The initial mixture is added to the feed hopper of a twin-screw extruder. The material stays in the high-temperature and high-shear zone for 2.0 minutes. The melt is extruded into strips through the die head, cooled and dried in a 27°C water bath, and cut into 3mm cylindrical particles by a pelletizer. The particles are then dried in hot air at 65°C for 4 hours to obtain a low-shrinkage refractory material.
[0102] The twin-screw extruder temperatures are: Zone 1 165℃, Zone 2 180℃, Zone 3 195℃, Zone 4 200℃, Die head 193℃, and screw speed 320rpm.
[0103] Example 12
[0104] This embodiment provides a method for preparing a low-shrinkage refractory material for cross-linked polyethylene power cables, specifically including the following steps:
[0105] Step S1: Preparation of initial mixture
[0106] Magnesium hydroxide, ammonium polyphosphate and zinc borate were mixed evenly in a mass ratio of 35:12:5 to obtain a flame retardant synergist for later use.
[0107] Pentaerythritol tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], ethylene bis-stearamide and 2-methylimidazole were mixed evenly in a mass ratio of 2:2:1 to obtain a processing aid for later use.
[0108] Weigh out the following by weight: 100 parts of POE, 30 parts of modified wollastonite prepared in Example 6, 50 parts of flame retardant synergist, and 1.0 part of processing aid. Add them to a high-speed mixer and mix at a low speed of 500 rpm for 5 minutes at room temperature. Then add 25 parts of maleic anhydride-grafted POE and 6 parts of phosphenanthrene epoxy derivative prepared in Example 9. Increase the speed to 1000 rpm and mix at a high speed for 5 minutes to obtain the initial mixture.
[0109] Step S2: Preparation of low-shrinkage refractory materials
[0110] The initial mixture is added to the feed hopper of a twin-screw extruder. The material stays in the high-temperature and high-shear zone for 2.5 minutes. The melt is extruded into strips through the die head, cooled and dried in a 30°C water bath, and cut into 4mm cylindrical particles by a pelletizer. The particles are then dried in hot air at 70°C for 5 hours to obtain low-shrinkage refractory material.
[0111] The twin-screw extruder temperatures are: Zone 1 170℃, Zone 2 185℃, Zone 3 200℃, Zone 4 205℃, Die head 195℃, and screw speed 350 rpm.
[0112] Comparative Example 1
[0113] The difference between this comparative example and Example 12 is that the use of maleic anhydride-grafted POE was omitted in step S1 when preparing the initial mixture.
[0114] Comparative Example 2
[0115] The difference between this comparative example and Example 12 is that, in step S1, when preparing the initial mixture, wollastonite whiskers are used in an equal amount to replace the modified wollastonite.
[0116] Comparative Example 3
[0117] The difference between this comparative example and Example 12 is that, in step S1, when preparing the initial mixture, an equal amount of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide is used to replace the phosphaphenanthrene epoxy derivative.
[0118] Performance testing:
[0119] Sample preparation: The low-shrinkage refractory granules prepared in Examples 10-12 and Comparative Examples 1-3 were molded on a flat vulcanizing machine at 170-180℃ and 10-15MPa for 5-10 minutes to make standard sheet samples with a thickness of 2±0.1mm. Then, they were cut into strip samples of 100mm×10mm for later use.
[0120] Heat shrinkage rate: The heat shrinkage rate of the low-shrinkage refractory standard sheet specimens prepared in Examples 10-12 and Comparative Examples 1-3 was tested according to standard GB / T 2951.13-2008 "General Test Methods for Insulation and Sheath Materials of Cables and Optical Fibers - Part 13: General Test Methods - Density Determination - Water Absorption Test - Shrinkage Test". The test temperature was 150℃, and the results were characterized by heat shrinkage rate, expressed in % (%).
[0121] Limiting oxygen index (LOI): The LIO of the low-shrinkage refractory strip specimens prepared in Examples 10-12 and Comparative Examples 1-3 was tested according to standard GB / T 2406.2-2009 "Determination of flammability of plastics by oxygen index method - Part 2: Room temperature test". The test environment was room temperature, and the LIO was used for characterization. The unit is % (%).
[0122] Tensile strength and elongation at break: The tensile strength and elongation at break of the low-shrinkage refractory materials prepared in Examples 10-12 and Comparative Examples 1-3 were tested according to standard GB / T 2951.11-2008 "General Test Methods for Insulation and Sheath Materials of Cables and Optical Fibers - Part 11: General Test Methods - Thickness and Dimensional Measurements - Mechanical Properties Tests". The test temperature was 23±2℃. The tensile strength and elongation at break were used for characterization, with units of MPa and % respectively.
[0123] Vertical flammability rating: The vertical flammability rating of the low-shrinkage refractory strip samples prepared in Examples 10-12 and Comparative Examples 1-3 was tested according to the standard GB / T 2408-2021 "Determination of flammability of plastics by horizontal and vertical methods". The test environment was room temperature, and the vertical flammability rating was used for characterization. The specific data are shown in Table 1 below.
[0124] Table 1 - Performance Test Data of Samples
[0125] Project Group Example 10 Example 11 Example 12 Comparative Example 1 Comparative Example 2 Comparative Example 3 Heat shrinkage rate / % 1.5 1.2 1.3 4.2 4.8 1.9 Limiting oxygen index / % 32.0 34.5 33.2 28.5 27.8 30.0 Tensile strength / MPa 14.5 16.2 15.6 10.2 8.6 13.5 Elongation at break / % 306 325 310 205 165 275 Vertical Combustion Rating / Class V-0 V-0 V-0 V-2 V-1 V-1
[0126] Comparative analysis of the data in Table 1 shows that the low-shrinkage refractory material prepared by this invention has a thermal shrinkage rate of 1.2%, a limiting oxygen index of 34.5%, a tensile strength of 16.2 MPa, an elongation at break of 325%, and a vertical burning rating of V-0. All of these data are superior to those of the comparative example.
[0127] In Comparative Example 1, after removing maleic anhydride-grafted polyolefin, the free amino groups and terminal epoxy groups of the phosphoranone epoxy derivative on the surface of the modified wollastonite lost their anhydride pairing sites. During the melt extrusion stage, amide and ester crosslinking networks could not be formed. Only weak physical interactions existed between the inorganic whiskers and the polyolefin matrix. When heated, the interface debonding caused the molecular chain slippage to become unrestrained, resulting in a significant increase in thermal shrinkage. The weakening of the interface adhesion simultaneously led to a decrease in mechanical properties. The lack of crosslinking network resulted in a non-dense char structure during combustion, reducing flame retardant performance.
[0128] In Comparative Example 2, after replacing modified wollastonite with unmodified wollastonite, the whisker surface lacked epoxy group reaction sites, making it impossible to form a core-shell coating structure with terminal amino polysiloxanes. There was no chemical bond bridging between the inorganic phase and the organic matrix, and the whisker agglomeration due to surface energy mismatch led to stress concentration points. The anisotropic physical pinning effect was lost, and the disorientation slip of the molecular chains intensified upon heating, significantly increasing the thermal shrinkage rate. Agglomerates caused interfacial defects, resulting in a significant deterioration of mechanical properties. Uneven dispersion of the flame retardant weakened the synergistic effect, leading to a decrease in flame retardant performance.
[0129] In Comparative Example 3, after replacing the phosphenanthrene epoxy derivative with a free phosphorus-containing flame retardant, although the chemical anchoring network of modified wollastonite and anhydride-functionalized polyolefin was retained, the phosphorus-containing units could not bond to the matrix network due to the lack of reactive epoxy end groups. During processing and service, the free phosphorus-containing components migrated and precipitated, resulting in a decrease in gas-phase flame retardant efficiency and a reduction in limiting oxygen index. The free flame retardant had insufficient compatibility with polyolefin, which damaged the matrix continuity and slightly reduced mechanical properties. The condensed phase-gas phase synergistic flame retardant system was unbalanced, and the vertical combustion performance deteriorated.
[0130] The preferred embodiments of the present invention disclosed above are merely illustrative of the invention. These preferred embodiments do not exhaustively describe all details, nor do they limit the invention to specific implementations. Clearly, many modifications and variations can be made based on the content of this specification. This specification selects and specifically describes these embodiments to better explain the principles and practical applications of the invention, thereby enabling those skilled in the art to better understand and utilize the invention. The invention is limited only by the claims and their full scope and equivalents.
Claims
1. A low-shrinkage refractory material for cross-linked polyethylene power cables, characterized in that, It comprises the following components by weight: 80-100 parts POE, 20-30 parts modified wollastonite, 4-6 parts phosphenanthrene epoxy derivative, 18-25 parts maleic anhydride-grafted POE, 35-50 parts flame retardant synergist, and 0.5-1.0 parts processing aid; wherein the flame retardant synergist is composed of magnesium hydroxide, ammonium polyphosphate, and zinc borate in a mass ratio of 25-35:8-12:3-5; The modified wollastonite is prepared by: placing amino-terminated polydimethylsiloxane and xylene in a reaction vessel and stirring, adding epoxy-modified wollastonite whiskers, heating the reaction vessel to 75-85℃, keeping it at that temperature and stirring for 4-5 hours, and then processing it to obtain the modified wollastonite. The preparation method of the phosphenanthrene epoxy derivative is as follows: 9,10-dihydro-9-oxa-10-phosphenanthrene-10-oxide, allyl glycidyl ether and toluene are placed in a reaction vessel under nitrogen atmosphere and stirred. The reaction vessel is heated to 90-100℃ and kept at this temperature for 5-7 hours. The phosphenanthrene epoxy derivative is then obtained after post-treatment.
2. The low-shrinkage refractory material for cross-linked polyethylene power cables according to claim 1, characterized in that, The ratio of the amino-terminated polydimethylsiloxane, xylene, and epoxy-modified wollastonite whiskers is 1-2g:10-20mL:2-4g.
3. The low-shrinkage refractory material for cross-linked polyethylene power cables according to claim 1, characterized in that, The ratio of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, allyl glycidyl ether, and toluene is 1-2 g: 0.45-0.50 g: 8-12 mL.
4. The low-shrinkage refractory material for cross-linked polyethylene power cables according to claim 1, characterized in that, The epoxy-modified wollastonite whiskers are prepared by the following steps: A1. Place wollastonite whiskers and hydrochloric acid aqueous solution in a reaction vessel and stir. Heat the reaction vessel to 30-50℃ and stir for 0.5-1h. Post-treatment yields epoxy-modified wollastonite whisker precursor. A2. Place γ-glycidyl etheroxypropyltrimethoxysilane, tetraethyl orthosilicate, ethanol, deionized water and glacial acetic acid aqueous solution in a reaction vessel and stir at room temperature for 0.5-1 h to obtain epoxy-containing polysiloxane sol. A3. Place the epoxy-modified wollastonite whisker precursor and the epoxy-containing polysiloxane sol in a reaction vessel and stir. Heat the reaction vessel to 55-65℃ and keep it at that temperature for 2-4 hours. After post-treatment, epoxy-modified wollastonite whiskers are obtained.
5. The low-shrinkage refractory material for cross-linked polyethylene power cables according to claim 4, characterized in that, In step A1, the ratio of wollastonite whiskers to hydrochloric acid aqueous solution is 1-2g:8-15mL, and the concentration of hydrochloric acid aqueous solution is 0.3-0.5mol / L.
6. The low-shrinkage refractory material for cross-linked polyethylene power cables according to claim 5, characterized in that, In step A2, the ratio of the amounts of γ-glycidoxypropyltrimethoxysilane, tetraethyl orthosilicate, ethanol, deionized water and glacial acetic acid aqueous solution is 1.5-2.5g:0.2-0.5g:30-50mL:2-4mL:0.03-0.05g, and the concentration of the glacial acetic acid aqueous solution is 3-5wt%.
7. The low-shrinkage refractory material for cross-linked polyethylene power cables according to claim 6, characterized in that, In step A3, the ratio of the epoxy-modified wollastonite whisker precursor to the epoxy-containing polysiloxane sol is 8-10g:200-300mL.